Gargling with red grape (Vitis Vinifera) infused water to stabilize saliva pH, is it effective? - Sofian, Rizki; Ngatemi, Ngatemi; Muliawati, Dian; Aurelia, Pradiesta (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: Saliva plays a crucial role in maintaining the pH balance of the mouth, preventing enamel demineralization and caries. While conventional mouthwashes are often used to stabilize pH, their chemical content can cause side effects such as irritation and dry mouth. Alternatively, fruits can be used to help maintain pH balance naturally. These fruits contain bioactive compounds with antioxidant and antimicrobial properties that support oral health. Objective: To analyze the effectiveness of red grape infused water in stabilizing saliva pH. Methods: This study employed a pre-experimental design with a pretest-posttest one-group design. The research was conducted on students at SMP Pattimura Jagakarsa, South Jakarta. The sampling technique used proportional stratified sampling involving 60 students. The research instrument consisted of saliva pH measurement sheets and data were analyzed using the Wilcoxon test. Results: gargling with red grape infused water was effective in stabilizing saliva pH in the oral cavity, with a p-value of 0.000. Conclusion: gargling with red grape infused water is effective in stabilizing saliva pH in the oral cavity.